HepaDisk – A new quality of life questionnaire for HCV patients. Issue 7 (July 2019) - Fagiuoli, Stefano; Caporaso, Nicola; Morisco, Filomena; Buelli, Fabio; Gualberti, Giuliana; Saragaglia, Valeria; Chessa, Luchino; Corti, Giampaolo; Maida, Ivana; Mastroianni, Claudio M.; Pirisi, Mario; Russo, Francesco P.; et al.
Abstract: Background: Since most patients with hepatitis C virus (HCV) infection now receive treatment irrespective of liver disease severity, special attention to patient quality of life (QoL), including psycho-social aspects, is required. No QoL questionnaire is specific for patients with HCV. Aims: To develop and validate a short Italian questionnaire (HepaDisk) assessing the QoL of patients affected by HCV with intuitive graphic results that is understandable by patients and physicians. Methods: A questionnaire, drafted by a steering committee, underwent a Delphi survey. A multicenter, observational study was conducted to validate the developed HepaDisk versus other tools (CLDQ-I, SF-36, WPAI:HCV), and to evaluate its correlation with disease severity in Italian patients with HCV. Results: The 10-item questionnaire was validated in 214 patients. HepaDisk showed a high correlation with CLDQ overall score and WPAI:HCV activity impairment (Spearman's rank correlation: 0.651 and 0.595, respectively) and a lower correlation with SF-36. Strong internal consistency (Cronbach coefficient: 0.912), good test–retest reliability (Pearson's correlation coefficient: 0.789; 95% CI, 0.714–0.865), and responsiveness to changes among improved patients were demonstrated. Conclusion: HepaDisk is a reliable and user-friendly tool that can monitor disease impact on patient QoL over time, providing a visual representation easily understandable by both patients and physicians.